Abundance of Light‐Absorbing Anthropogenic Iron Oxide Aerosols in the Urban Atmosphere and Their Emission Sources. Issue 15 (3rd August 2018) - Ohata, Sho; Yoshida, Atsushi; Moteki, Nobuhiro; Adachi, Kouji; Takahashi, Yoshio; Kurisu, Minako; Koike, Makoto
Abstract: Light‐absorbing iron oxide (FeO x ) aerosols such as magnetite contribute to shortwave atmospheric heating and possibly affect the biogeochemical cycle. However, their atmospheric abundance and emission sources are poorly understood. In this study, we quantified the abundance and mixing states of FeO x at two urban sites in Tokyo and Chiba, Japan, using a modified single‐particle soot photometer and filter‐based instruments. At both sites, the majority of the FeO x were of anthropogenic origin in the form of aggregated magnetite nanoparticles, and their concentrations generally correlated with those of black carbon (BC) and carbon monoxide. In Chiba, where the observatory was located near an integrated steel plant, we observed distinctly high FeO x concentrations and high FeO x /BC concentration ratios when the air mass passed through the plant. From the observed FeO x plumes with the mass equivalent diameter range of 170–2, 100 nm, we made an estimate of their emission flux to be approximately 0.012% of the crude steel production, assuming that a Gaussian plume approximation was applicable to our data analysis. Meanwhile, in Tokyo, where the observatory was 20–40 km northwest of steel plants, the FeO x concentrations and FeO x /BC ratios showed clear diurnal variations and depended little on wind direction. This indicates that other human activities also locally produce FeO x aerosols in Tokyo. Our data imply that although steel plant activities emit a large amount of FeO x, emissions from other anthropogenic sources, for example, motor vehicles, have a major contribution to the abundance of FeO x aerosols at the regional and global scales. Key Points: Light‐absorbing FeO x (magnetite) particles are ubiquitous in the urban atmosphere, and their concentrations are generally correlated with BC concentrations The emission flux of FeO x aerosols from a steel plant is roughly estimated to be 0.49 Gg/yr, corresponding to 0.012% of the crude steel production of the plant Diurnal variations in the FeO x /BC concentration ratio in Tokyo suggest that local human activities such as traffic are dominant emission sources of FeO x